Hardware-In-the-Loop Simulation of Time-Delayed Anti-Swing Controller for Quadrotor with Suspended Load - Hanafy M. Omar (Applied Sciences, 2022)
Quadrotor flying vehicles with suspended loads have a lot of applications, such as mine detection and transferring loads for delivery, or through places where ground vehicles cannot reach. In these applications, the payload will be suspended underneath the vehicle and it is subjected to large oscillations due to external disturbances or the acceleration of the vehicle itself. These oscillations add additional forces and moments to the quadrotor, and this deteriorates its performance and stability. In this paper, we developed a hardware-in-the-loop (HIL) simulation platform for a quadrotor with a suspended load system using Gazebo. The developed platform can be used to understand the dynamics of the system and design control systems to suppress the oscillation of the suspended load. An anti-swing controller that is based on time-delayed feedback of the load swing angles is implemented in the designed HIL environment to show the usefulness of the newly developed system and the effectiveness of the anti-swing controller.